SPOSOBY KSZTAŁCENIA NAUCZYCIELI JĘZYKÓW SPECJALISTYCZNYCH: OD RZECZYWISTOŚCI EDUKACYJNEJ DO ROZWIĄZAŃ SYSTEMOWYCH - Gajewska, Elżbieta; Sowa, Magdalena (Neofilolog, 2019)
The job of the teacher of Language for Specific Purposes (LSP) requires the ability to teach learners of diverse profiles. Diversity of target groups in training entails diversity of language and learning needs. This paper aims to answer the question: how should LSP teachers be educated so that they can fulfil these needs and expectations? It is suggested that this can be done by preparing and implementing a suitable teaching programme which takes into account the specific character of different educational contexts. The reflections presented here are based on analysis of the Polish educational situation in LSP training. On the basis of these observations, several practice-oriented proposals will be formulated, which could be implemented in the process of language teacher training. Consideration is given, among other issues, to the pedagogical instruction that future LSP teachers need (which depends on the educational context of their future work), the scope of specialist knowledge in the given field that they will find indispensable, and the amount of knowledge of discourse and genre analysis with which they have to be equipped.